PENGEMBANGAN MODUL AJAR KEBUTUHAN DAN KEINGINAN BERBASIS PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA KELAS IV SD - Andini, Listanti Putri; Rusmawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Developing effective communication abilities represents a fundamental educational objective at the elementary level. Nevertheless, social studies instruction in primary schools frequently maintains a teacher-dominated approach, limiting opportunities for students to cultivate their communicative competencies. This investigation focuses on designing an instructional module centered on the needs and wants concept, utilizing Project-Based Learning (PjBL) methodology to enhance fourth-grade students' communication capabilities. The study employs Research and Development (R&D) methodology, implementing the ADDIE framework encompassing five sequential phases: analysis, design, development, implementation, and evaluation. Twenty-five fourth-grade students from SDN Ngemplak 3 participated as research subjects. Data collection utilized expert validation instruments, communication skills assessment tools, and student feedback questionnaires. Validation outcomes revealed that the developed module achieved a mean score of 3.57 on a four-point scale, classified as